STRATEGIC MARKETING VECTOR OF SOCIALLY RESPONSIBLE PROJECTS IN THE CIRCULAR ECONOMY OF DIGITAL ERA - Кононенко, Яна (SWorldJournal, 2025)
The article examines the strategic marketing vector of socially responsible projects operating within the framework of a circular economy in the context of digital transformation.The impact of digital technologies on marketing strategies aimed at promoti